Entrepreneurship through Digital Transformation and Social Changes - CULIC, Lorina; HOSU, Ioan; VOINA, Andreea Nicoleta (Presa Universitară Clujeană, 2022)
This volume, Entrepreneurship through Digital Transformation and Social Changes, represents the conference outcome and embodies the authors’ efforts delivered through 36 articles, structured into four sections. The contributions blend in a diverse approach stemming not just from the variety of topics tackled, but also through the perspectives of theoretical and empirical work, elaborated in English or Romanian, fitting both extensive papers and extended abstracts thoroughly discussed in the panels and workshops of the conference.